2013
DOI: 10.1246/cl.130185
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis Induced by the Helical Molecular Arrangement in the Chiral Crystal of Achiral Tris(2-hydroxyethyl) 1,3,5-Benzenetricarboxylate in Conjunction with Asymmetric Autocatalysis

Abstract: 5-Pyrimidyl alkanol with an enantiomeric excess of up to >99.5% was formed using chiral crystals of achiral tris(2-hydroxyethyl) 1,3,5-benzenetricarboxylate as a chiral initiator.In the enantioselective addition of diisopropylzinc to pyrimidine-5-carbaldehyde, the helicity of the molecular arrangement of achiral tricarboxylate in the crystalline state could be successfully used as a source of chirality to afford enantioenriched alkanol in conjunction with asymmetric autocatalysis with amplification of enantiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 40 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…In addition, chiral crystals composed of achiral Nbenzoylglycine, [44] 2-thenoylglycine, [45] cocrystals composed of two achiral compounds, [46] benzil, [47] tetraphenylethylene, [48] ethylenediammonium sulfate, [49] benzenecarboxylate, [50] and 2,6-di-tert-butyl-p-cresol (BHT) [51] are found to be chiral triggers of asymmetric autocatalysis (Scheme 6).…”
Section: Other Chiral Organic Crystalsmentioning
confidence: 99%
“…In addition, chiral crystals composed of achiral Nbenzoylglycine, [44] 2-thenoylglycine, [45] cocrystals composed of two achiral compounds, [46] benzil, [47] tetraphenylethylene, [48] ethylenediammonium sulfate, [49] benzenecarboxylate, [50] and 2,6-di-tert-butyl-p-cresol (BHT) [51] are found to be chiral triggers of asymmetric autocatalysis (Scheme 6).…”
Section: Other Chiral Organic Crystalsmentioning
confidence: 99%
“…Enantiomorphous crystals formed from achiral N-benzoylglycine (hippuric acid) [96], 2-thenoylglycine [97], certain chiral cocrystals consisting of two achiral compounds [98], benzil [99], tetraphenylethylene [100], ethylenediammonium sulfate [101], aromatic triester [102], and 2,6-di-tert-butyl-p-cresol (BHT) [103] serve as chiral initiators of asymmetric autocatalysis (Scheme 7). It should be added that a chiral crystal composed of a racemic serine initiates asymmetric autocatalysis.…”
Section: Chiral Crystals Formed From Achiral Organic Compoundsmentioning
confidence: 99%
“…It was also found that enantiomorphous crystals composed of achiral N -benzoylglycine, 84) N -(2-thienylcarbonyl)glycine, 85) cocrystal of tryptamine and p -chlorobenzoic acid, 86) benzil, 87) tetraphenylethylene, 88) ethylenediamine sulfate, 89) benzene triester 90) and 2,6-di- t -butyl- p -cresol (BHT) 91) act as chiral triggers for asymmetric autocatalysis of 1c . Thus, asymmetric autocatalysis could serve as a macroscopic observation tool of molecular-level information on the structure of crystal surfaces.…”
Section: Examination Of the Origins Of Chirality By Using Asymmetric mentioning
confidence: 99%